The Influence of Social Media Marketing, Price Discount, and Online Customer Review on Purchase Intention of Skintific Products on Shopee Live - Bernice Darros Jennedy; Haris Maupa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the influence of social media marketing, price discounts, and online customer reviews on the purchase intention of Skintific products on Shopee Live. This study uses a quantitative approach with sample selection using purposive and non-probability sampling techniques. Data were collected using an online questionnaire, namely Google Forms. Based on 250 data points successfully collected, the data was then processed using SmartPLS 4th. By using SmartPLS analysis, the results of the outer loading analysis show that all variables used in this study, such as social media marketing, price discounts, online customer reviews, and purchase intentions, are declared to meet the validity and reliability test criteria (Cronbach's Alpha> 0.05). When a study is declared to have passed the outer loading test, it can be continued to the inner model test stage to determine the influence given by exogenous variables on endogenous variables. Through the inner model test, it can be seen that all variables have a positive and significant effect on purchase intention.